Immediate vitrectomy as a method of choice in the treatment of endophthalmitis - Stankiewicz, Andrzej; Robaszkiewicz, Jacek; Kosatka, Mariusz (Klinika Oczna / Acta Ophthalmologica Polonica, 2005)
This study is evaluation of the results of surgical treatment in case of postoperative endophthalmitis. The results of 16 pars plana vitrectomies in 16 patients with clinical evidencs of postoperative endophthalmitis were analyzed. Successful management of postoperative endophthalmitis depends on timely diagnosis and institution of appropriate therapy.